Genetically Modified Insects for Pest Control: An Update. (1st April 2012) - Morrison, Neil; Alphey, Luke
As human populations continue to grow around the world, demand for food and the number of people at threat from vector-borne diseases increases. Insecticides have long been seen as the mainstay of control of insects important for agriculture and human health, but are becoming compromised by difficulties with discovery and development of novel chemistry, the loss of and restrictions on the use of existing products, and development of resistance in target pests. Growers and public health authorities are increasingly looking for other options to replace or supplement synthetic insecticides, or to prolong their useful life. Alternative control methods, which are diverse in action and environmentally sustainable, include beneficial organisms (predators and parasitoids), plant extracts, biopesticides, the sterile insect technique (SIT, mass-release of radiation-sterilised pest insects) and transgenic crops. The past decade has seen a massive increase in their uptake, and there is increasing demand for these and similar techniques as integrated pest management (IPM) practices become more prevalent. One new control method showing promise is based on the release of transgenic insect strains to control the target pest. First proposed over a decade ago, Release of Insects Carrying a Dominant Lethal (RIDL®) is similar in principle to the SIT: by releasing large numbers of a sterile pest insect species – one that produces non-viable offspring – over a sufficient period of time, the wild population's reproductive potential will be hampered and eventually it crashes. SIT is not new and has provided decades of successful pest control, but transgenic methods (i.e. RIDL) offer substantial improvements to existing programmes, and are likely to widen the application of the SIT to a broader range of pests and a wider scale of use.